Practice the questions of McGraw Hill Math Grade 8 Answer Key PDF Lesson 14.2 Function Tables to secure good marks & knowledge in the exams.
McGraw-Hill Math Grade 8 Answer Key Lesson 14.2 Function Tables
Exercises
CALCULATE
Fill in the corresponding values of y for the given x value in the function table.
Question 1.
y = x + 1
Answer:
Explanation:
Filled in the corresponding values of y for the given equation y = x + 1,
x value in the function table as if x = 0 then y = 0 + 1 = 1,
if x = 1 then y = 1+1 = 2, if x = 2 then y = 2+ 1 = 3,
if x = 3 then y = 3 + 1 = 4, if x = 4 then y = 4 + 1 = 5 and
if x = 5 then y = 5 + 1 = 6 above.
Question 2.
y = 2x + 2
Answer:
Explanation:
Filled in the corresponding values of y for the given equation y = 2x + 2,
x value in the function table as if x = -2 then y = 2 X -2 + 2 = -4 + 2 = -2,
if x = -1 then y = 2 X -1 + 2 = -2 + 2 = 0,
if x = 0 then y = 2 X 0 + 2 = 0 + 2 = 2,
if x = 1 then y = 2 X 1 + 2 = 2 + 2 = 4,
if x = 2 then y = 2 X 2 + 2 = 4 + 2 = 6 and
if x = 3 then y = 2 X 3 + 2 = 6 + 2 = 8.
Question 3.
y = x – 4
Answer:
Explanation:
Filled in the corresponding values of y for the given equation y = x – 4,
x value in the function table as if x = 0 then y = 0 – 4 = -4,
if x = 1 then y = 1 – 4 = -3, if x = 4 then y = 4 – 4 = 0,
if x = 6 then y = 6 – 4 = 2, if x = 8 then y = 8 – 4 = 4 and
if x = 10 then y = 10 – 4 = 6.
Question 4.
y = 2x – 3
Answer:
Explanation:
Filled in the corresponding values of y for the given equation y = 2x – 3,
x value in the function table as
if x = -1 then y = 2 X -1 – 3 = -2 – 3 = -5,
if x = 0 then y = 2 X 0 – 3 = 0 – 3 = -3,
if x = 1 then y = 2 X 1 – 3 = 2 – 3 = -1,
if x = 2 then y = 2 X 2 – 3 = 4 – 3 = 1,
if x = 3 then y = 2 X 3 – 3 = 6 – 3 = 3 and
if x = 5 then y = 2 X 5 – 3 = 10 – 3 = 7.
Question 5.
y = 2x + 1
Answer:
Explanation:
Filled in the corresponding values of y for the given equation y = 2x + 1,
x value in the function table as
if x = -2 then y = 2 X -2 + 1 = -4 + 1 = -3,
if x = 1 then y = 2 X 1 + 1 = 2 + 1 = 3,
if x = 0 then y = 2 X 0 + 1 = 0 + 1 = 1,
if x = 2 then y = 2 X 2 + 1 = 4 + 1 = 5,
if x = 4 then y = 2 X 4 + 1 = 8 + 1 = 9 and
if x = 6 then y = 2 X 6 + 1 = 12 + 1 = 13.
Question 6.
y = \(\frac{1}{2}\)x + 1
Answer:
Explanation:
Filled in the corresponding values of y for the given equation
y = \(\frac{1}{2}\)x + 1, x value in the function table as
if x = -4 then y = \(\frac{1}{2}\) X -4 + 1= -2 + 1 = -1,
if x = -2 then y = \(\frac{1}{2}\) X -2 + 1 = 2 + 1 = 0,
if x = 0 then y = \(\frac{1}{2}\) X 0 + 1 = 0 + 1 = 1,
if x = 2 then y = \(\frac{1}{2}\) X 2 + 1 = 1 + 1 = 2,
if x = 4 then y = \(\frac{1}{2}\) X 4 + 1 = 2 + 1 = 3 and
if x = 6 then y = \(\frac{1}{2}\) X 6 + 1 = 3 + 1 = 4.
Identify the function by looking at the ordered pairs (x, y) in the function table.
Question 7.
Answer:
f(y) = x + 2,
Explanation:
If we see the values of y it is 2 more than x in each case,
therefore function of the ordered pairs is f(y) = x + 2.
Question 8.
Answer:
f(y) = 2x + 9,
Explanation:
If we see the values of y it is 2x and 9 more in each case,
therefore function of the ordered pairs is f(y) = 2x + 9.
Question 9.
Answer:
f(y) = x2 + 2,
Explanation:
If we see the values of y it is square of x and 2 more in each case,
therefore function of the ordered pairs is f(y) = x + 2.
Question 10.
Answer:
f(y) = x3,
Explanation:
If we see the values of y it is cube of x,
therefore function of the ordered pairs is f(y) = x3.
Complete the function table and then graph the function.
Question 11.
y = 3x – 3
Answer:
Explanation:
Completed the function y = 3x – 3 in the table for values of
y for x value in the function table as
if x = -2 then y = 3 X -2 – 3 = -6 – 3 = -9,
if x = -1 then y = 3 X -1 – 3 = -3 – 3 = -6,
if x = 0 then y = 3 X 0 – 3 = 0 – 3 = -3,
if x = 1 then y = 3 X 1 – 3 = 3 – 3 = 0,
if x = 2 then y = 3 X 2 – 3 = 6 – 3 = 3 and
if x = 3 then y = 3 X 3 – 3 = 6.
Question 12.
y = x2
Answer:
Explanation:
Completed the function y = x2 in the table for values of
y for x value in the function table as
if x = -3 then y = (-3)2 = – 3 X – 3 = 9,
if x = -2 then y = (-2)2 = -2 X -2 = 4,
if x = -1 then y = (-1)2 = -1 X -1 = 1,
if x = 0 then y = (0)2 = 0 X 0 = 0,
if x = 1 then y = (1)2 = 1 X 1 = 1,
if x = 2 then y = (2)2 = 2 X 2 = 4 and
if x = 3 then y = (3)2 = 3 X 3 = 6.